Pinkalicious : tutu-rrific (New York: Harper, 2014)
Pinkalicious is excited to go to ballet class with her best friend, Alison, but there is a mix-up and she ends up in the big kids' class.
2.3
K-3
Keywords: Pink -- Juvenile fiction; Ballet -- Juvenile fiction; Pink -- Fiction; Ballet -- Fiction; Pink -- Fiction; Ballet -- Fiction; Ballet -- Fiction; Friendship -- Fiction; Pink -- Fiction; Readers (Elementary)